Cardiopulmonary Arrest and Resuscitation in the Prone Patient: An Adult Simulation Case for Internal Medicine Residents - Tejas Sinha; Kyle Stinehart; Cashay Moorer; Carleen Spitzer (Association of American Medical Colleges, 2021)
Introduction Acute respiratory distress syndrome (ARDS) is present in approximately 10% of ICU admissions and is associated with great morbidity and mortality. Prone ventilation has been shown to improve refractory hypoxemia and mortality in patients with ARDS. Methods In this simulation, a 70-year-old male had been transferred to the ICU for ARDS and was undergoing scheduled prone ventilation as part of his care when he experienced a cardiopulmonary arrest secondary to a tension pneumothorax. Learners demonstrated how to manage cardiac arrest in a prone patient and subsequently identified and treated the tension pneumothorax that was the cause of his initial arrest. This single-session simulation for internal medicine residents (PGY 1-PGY 4) utilized a prone mannequin connected to a ventilator in a high-fidelity simulation center. Following the simulation, facilitators led a team debriefing and reviewed key learning objectives. Results A total of 103 internal medicine residents participated in this simulation. Of those, 43 responded to a postsimulation survey. Forty-two of 43 agreed or strongly agreed that all learning objectives were met, that the simulation was appropriate for their level of training, and that their participation would be useful for their future practice. Discussion We designed this simulation to improve learners' familiarity with prone cardiopulmonary resuscitation and to enhance overall comfort with cardiac arrest management. Postsimulation survey results and debriefings revealed that the simulation was a valuable education opportunity, and learners felt that their participation in this simulation would be helpful in their future practice.